QUORUM QUENCHING POTENTIALS OF PROBIOTIC ENTEROCOCCUS DURANS LAB38 AGAINST METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - Boopathi, Seenivasan; Selvakumar, Gopal; SIVAKUMAR, NATESAN (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: he focus of this study was to explore the nuance strategy to combat the virulence factors of the pathogens by probiotic Enterococcus durans LAB38 Methods: Probiotic attributes was determined by bile salt tolerance (0.5%) and Artemia gnotobiotic assay. Quorum sensing (QS) inhibitory activity of the supernatant and ethyl acetate (EA) extract of LAB38 was evaluated by using the indicator strains, includes Chromobacterium violaceum CV026 (mini-Tn5 mutant of ATCC 31532), methicillin resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa (PA). Reporter strains, Vibrio harveyi BB170 (luxN mutant), BB886 (luxP mutant) and Escherichia coli pSB401 (pACYC184- derived) were used for bioluminescence-based target specificity analysis. GC-MS analysis of EA extract was performed using standard protocol. Results: LAB38 has shown bile salt tolerance and positive probiotic effect towards Artemia salina. In addition, 100 µg/ml EA extract has significantly reduced the violacein production (37 ± 1.4%) in CV026, biofilm formation in MRSA (94 ± 0.9 %) and PA (22 ± 0.08%). Further, 200 µg/ml of EA extract has shown inhibition against both autoinducer-1 and autoinducer-2 mediated QS system. Bioluminescence inhibition is directly proportional to the time of exposure. GC-MS result revealed that bromine, sulphur containing molecule and azulene derivative were found in the EA extract. Conclusion This is the first report on probiotic Enterococcus durans for quorum quenching activity. Hence, the bacterium could be used for future therapeutics application. Keywords: Autoinducer, Biofilm, Methicillin resistant Staphylococcus aureus, Quorum quenching, Probiotics, CV026.